2017
DOI: 10.1111/rec.12539
|View full text |Cite
|
Sign up to set email alerts
|

Rare plant translocation between mineral islands in Biebrza Valley (northeastern Poland): effectiveness and recipient site selection

Abstract: We carried out translocations of three rare plants that inhabit mineral islands in the marshy Biebrza Valley in order to create alternative populations and facilitate connectivity between existing subpopulations. The species chosen were Iris aphylla and two orchids: Cypripedium calceolus and Cephalanthera rubra. Thirty soil monoliths with vegetative orchid plants or parts of I. aphylla rhizomes were dug out and transplanted to three different sites on new mineral islands (half in 2012 and half in 2013). Prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…1). Although in rhizomatous plants, larger outplants have a higher chance of survival and better growth (Brzosko et al 2018), it is recommended to use outplants of different ages/life stages in the translocations of long-lived species into spatially and temporarily varying environments (Albrecht & Maschinski 2012). For this reason, and due to the limited availability of large rhizomes, each set comprised the following size classes (number in parentheses): <5 g ( 14), 5-10 g (10), 10-20 g (23), 20-30 g (10), 30-40 g (3), and >40 g (2).…”
Section: Study Species and Translocation Sitementioning
confidence: 99%
“…1). Although in rhizomatous plants, larger outplants have a higher chance of survival and better growth (Brzosko et al 2018), it is recommended to use outplants of different ages/life stages in the translocations of long-lived species into spatially and temporarily varying environments (Albrecht & Maschinski 2012). For this reason, and due to the limited availability of large rhizomes, each set comprised the following size classes (number in parentheses): <5 g ( 14), 5-10 g (10), 10-20 g (23), 20-30 g (10), 30-40 g (3), and >40 g (2).…”
Section: Study Species and Translocation Sitementioning
confidence: 99%
“…Several studies and reviews have shown that species with highly restricted ranges are disproportionately at risk of extinction (Mace et al ; Pimm et al ), particularly if there are other threats such as habitat loss (Schemske et al ; Brooks et al ; Mace et al ; Brummitt et al ). Restoration of rare species populations is considered to be an appropriate response to counter such threats, but requires a careful, evidence‐based, and information‐driven approach (Brzosko et al ). The approximately 300 km 2 range of the narrow vulnerable endemic leaf succulent species Juttadinteria albata (L. Bolus) L. Bolus (Mesembryanthemaceae) is centered on the Sendelingsdrif Diamond Mine on the Namibian bank of the lower Orange River (Loots ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the risks of failure associated with restoration in general and with arid land restoration specifically (Aronson et al ), it is important to approach such an initiative with caution. As is the case with reintroduction of plant species anywhere (Dalrymple et al ; Brzosko et al ), particularly for species with highly restricted ranges, the optimization of habitat conditions after mining is likely to be key to success. Previous unpublished studies defined both the geographic range of J. albata (Burke ) and general landscape categories in the study area (Fortuin ), but the species' specific habitat preferences and relationships with key environmental variables were unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Restoration of endangered orchids through transplantation is becoming increasingly common in biological conservation (Godefroid et al 2011;Brzosko et al 2018). However, assessments of restoration success are rare despite their usefulness in species conservation (Brzosko et al 2018). Restoration is successful if a reproductive, self-sustaining population forms (Gale 2007;Reiter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the location selected for restoration must exhibit the ecological properties required by a given target species (Akeroyd & Wyse Jackson ; Jusaitis ; Seddon et al ). Few studies have directly investigated the environmental conditions prior to site selection, and existing research on this topic typically includes only a limited number of factors (Reiter et al ; Brzosko et al ).…”
Section: Introductionmentioning
confidence: 99%